Numerical Approximation Of Riccati Type Differential Equations - Ahmad Fadly Nurullah bin Rasedee; Mohamad Hasan Abdul Sathar; Norizarina Ishak; Siti Raihana Hamzah; Nur Amalina Jamaludin (Akademi Sains Malaysia, 2024)
Non-Indexed Publication